(untitled) (Fiep Bulletin - online, 2015)
Stress is considered nowadays one of the main problems of public health, being able to cause several physiological imbalances throughout all the human body. By a combination of several factors, alterations can appear due to homeostasis break. The most common diseases are the cardiovascular, ulcers and susceptibility to infectious diseases like the flu. Cronic exposure to stress causes physical exhaustion able to disturb the internal balance damaging the life quality of the individuals. Objective: Connect the phases of stress experienced by the volunteers with their personal and socioeconomic characteristics and the influence of these factors in the susceptibility to the flu in the period of one year. Methods: It is a descriptive, transversal and quantitative study, performed with 539 people through a semi-structured questionnaire. The data based on the symptomatology were compiled and graphics of simple frequency, expressed in numbers and percentages were presented. The ethical aspects were respected, according to the Resolution Nº 196/96 (CNS-MS) Results: It has been noted that most of the population didn`t know the difference between a flu and a cold. The majority of the volunteers present a profile of ages from 18 to 30 years old and family income inferior to 3 minimum wages, and most of them spend less than two hours in the traffic per day. 39% of the total corresponded with the alert phase and the percentage of volunteers that had the flu more than three times a year was of 35%. Comparing these rates with the socioeconomic profile, it has been verified that within the group with elementary school level, the percentage of individuals with more than five flus per year is 15.79%, which indicates there is an inclination for the occurrence of more flus in people with family income equivalent or inferior to three minimum wages and low life quality. We can associate higher susceptibility to the flu in the studied population with lower socioeconomic condition.